THE THEORETICAL ASPECTS OF WELL-BEING IN THE CONTEXT OF LIFELONG LEARNING - Odiņa, Indra; Zeide, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In 2006 the European Parliament and European Union Council has defined eight key competences for lifelong learning, necessary for personal fulfillment and development, active citizenship, social inclusion and employment. Since the economic crisis of 2008, the world is looking for new ways and methods to ensure the well-fare and reformulate the value of human life. Currently at EU level, one of the most important debates closely connected with the basic context of lifelong learning is on the dimensions of life quality.The desk study deals with the qualitative content analysis of the documents of EU, OECD, data of the projects of Office of National Statistics in Latvia, the U.K. and Germany, research of Ruff (1995), Rath and Harter (2010), Layard (2005), Rohr (2014), etc. The dimensions of life quality in different sources and by different authors have been defined similarly indicating that the qualitative indicators are as important as the quantitative. It is clear that the quality of life cannot be measured only by quantitative indicators such as income or birth / mortality. This article discusses the theoretical aspects of such dimension of life quality as well-being in different sources, compares and analyses them in the Latvian context.